Semiotics and communication. Theory of signs and codes - Escobar Zapata, Emérita (2014)
In this paper, we develop the theme of semiotics as the science that studies the processes of signification. As science explains and interprets verbal and nonverbal mechanisms used to communicate with the man, that is, to convey information about different realities; regularly does so through a range of signs. This is understandable, because in truth, the human being is a symbolic being, par excellence created, issued and interpreted signs, and in turn, organizes and systematizes through codes, in either case, culture is implicit. Without any doubt, to understand the nature of the human being and communication, one must understand the signs and codes. In this sense, for a better understanding and and we include a variety of examples, taken directly from users in a specific context.